2016
DOI: 10.1515/vzoo-2016-0062
|View full text |Cite
|
Sign up to set email alerts
|

Pecular Features of Hematopoiesis in the Liver of Mature and Immature Green Frogs (Pelophylax Esculentus Complex)

Abstract: The article describes characteristic features of the hematopoiesis in mature and immature green frogs (Pelophylax esculentus complex). Quantitative differences in liver myelograms were insignificant. However, in a sample of mature animals numerous significant correlations between the number of pigment inclusions in the liver and indicators of erythropoiesis and myelopoiesis were observed. Those correlations were absent in the immature frogs. We concluded that aft er the frogs’ breeding a lack of plastic resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Th e accumulations inside the liver include pigment cells and macrophages. In a healthy liver, pigment inclusions are used during blood formation and in non-specifi c immunity reactions (Akulenko, 2016). It was shown that the inclusion of pigments is also used in the course of hepatocyte repaire in the foci of necrosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Th e accumulations inside the liver include pigment cells and macrophages. In a healthy liver, pigment inclusions are used during blood formation and in non-specifi c immunity reactions (Akulenko, 2016). It was shown that the inclusion of pigments is also used in the course of hepatocyte repaire in the foci of necrosis.…”
Section: Resultsmentioning
confidence: 99%
“…According to our data, under conditions of moderate anthropogenic pollution, the synthesis of pigments in the liver of frogs and at the same time their use in protective reactions is stimulated (Akulenko, 2013). Th erefore, in some animals, the content of pigments in the liver increases, in others, on the contrary, it is reduced (Akulenko, 2013(Akulenko, , 2016. Fenoglio with co-authors (2005) noted the intensifi cation of the synthetic processes in the liver melano-macrophages under conditions of anthropogenic pollution.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, evidence was obtained that the liver pigment inclusions of the lake frog are used in liver repair processes after necrosis (Akulenko, 2013). The presence of specific repair mechanisms allows frogs to restore the liver after significant damage without replacing hepatocytes with fibrous formations that are characteristic of mammals (Akulenko, 2016). Thus, further study of amphibian-specific mechanisms of liver repair involving melanin, may be impotent for medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The number of pigment inclusions of the liver and other internal organs of poikilothermic vertebrates and the rate of their renewal can potentially be used as a marker of the degree of anthropogenic pollution (Akulenko, 2016;Pérez-Iglesias et al, 2016;de Gregorio et al, 2016;Barros et al, 2017). Therefore, a method that allows estimating the rate of exchange of liver pigments, determining the percentage of young and old pigment cells, can be useful for developing biological methods for monitoring environmental contamination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation